P927Electrophysiological features in children with premature ventricular contractions. (18th June 2020) - Alekseeva, K; Kruchina, T; Gordeev, O; Ginzburg, I; Novik, G; Egorov, D
Abstract: Background: Premature ventricular contractions (PVCs) is the one of the most frequent arrhythmias in children. There is no clear understanding regarding the causes of PVCs in children without structural heart diseases. There is also little information about the state of the conduction system (CS) of the heart in children with PVCs. Purpose:The aims of the study were to estimate the electrophysiological properties of the sinus node (SN) and atrioventricular node (AVN) in children with PVCs, and to evaluate the effect of atropine test on the frequency and nature of the PVCs. Methods: 167 children(54(32, 3%) girls and 113(67, 7%) boys with PVCs without structural heart disease were examined. Mean age at the time of the first examination was 14, 5 ± 5, 3years (6-18 years). Examination included: ECG, 24-hour Holter monitor (HM), echocardiogram, treadmill test, transesophageal pacing study (TEPS), atropine test.Results:The duration of the PVCs was 3, 3 ± 1, 5years (6-14 years). The burden of the PVCs was 7-29% according to HM data. 5(3%) children had syncope. Frequent PVCs were recorded in 43(25, 7%) patients, single PVC in 59 (35, 3%), and the rest of children did not have PVCs during TEPS. SN recovery time (SNRT) was 1118, 1 ± 292, 4ms (541-2300ms) which exceeded the age-dependent limit in 23(13, 7%) children. Corrected SNRT was 350, 1 ± 171, 1ms (41-1317ms), which exceeded the age-dependent limit in 15(8, 9%) children. Max.rate of 1:1 conduction through AVN was 166, 7 ± 39, 1 imp/min (90-220 imp/min); in 16(9, 6%) children it was less than 120 imp/min, while 8 (4, 8%) children had enhanced AV nodal conduction (more than 200imp/min). The effective refractory period (ERP) of AVN was 325, 1 ± 91, 7ms (190-650ms), exceeding the age norm in 18(10, 7%) children. 16(9, 6%) children had a discontinuous AV nodal conduction. The frequency of stimulation which suppressed PVCs was 100-160imp/min. Atropine test was performed in 100(59, 9%) children (0, 1% sol. Atropini sulfatis 0, 02 mg/kg IV). After administration of atropine the increase in heart rate constituted 7-131%, with an average of 57%. The SNRT was 665, 5 ± 154, 4 ms (406-1512ms), maximal rate of 1:1 conduction through AVN was 213, 2 ± 31, 9 imp/min (150-270 imp/min). Among patients who initially had PVCs during TEPS, after atropine test PVCs disappeared in 61(59, 8%) children, in 16(15, 7%) children there was a significant decrease, and 4(3, 9%) patients had an increase in the number of PVCs and episodes of stable ventricular bigeminy, and in 1(0.9%) child there were short runs of ventricular tachycardia (up to 8 QRS complexes).Conclusions: In children with PVCs normal electrophysiological parameters of cardiac CS were noted in most cases. In 35% of children there was a hypervagotonic influence on SN or AVN, and in 75, 5% cases there was a disappearance or decrease in PVCs after atropine test. This suggests that the preferential nature of PVCs in children without structural heart diseases is autonomic system dependent